2022
DOI: 10.1590/1806-9282.20220333
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic thiol-disulfide homeostasis in patients with lipoid proteinosis (Urbach-Wiethe syndrome)

Abstract: OBJECTIVE: Lipoid proteinosis is a rare autosomal recessive genetic dermatological disease that occurs due to the accumulation of hyaline material in the skin and mucous membranes. This study aimed to investigate whether dynamic thiol-disulfide homeostasis is a new marker of oxidative stress in patients suffering from lipoid proteinosis. METHODS: The study group involved 17 patients with lipoid proteinosis and 17 healthy controls with same gender and age. Native thiol, total thiol, disulfide levels, and thiol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… 22 , 23 Clinical studies have shown that the change in thiol-disulfide homeostasis can be used in the monitoring of many diseases or may play a role in the pathogenesis of the disease. 8 , 17 Therefore, it is important to determine the thiol-disulfide status in diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 , 23 Clinical studies have shown that the change in thiol-disulfide homeostasis can be used in the monitoring of many diseases or may play a role in the pathogenesis of the disease. 8 , 17 Therefore, it is important to determine the thiol-disulfide status in diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 3 It has been stated that oxidative stress, which occurs due to the deterioration in the homeostatic balance between oxidants and antioxidants, plays a role in the pathophysiology of many diseases. 3 , 8 There are many biochemical methods used to analyze the level of oxidative stress in biological systems. 9 Thiol disulfide balance, total oxidant status (TOS), and total antioxidant status (TAS) are widely recognized as key markers of oxidative stress.…”
Section: Introductionmentioning
confidence: 99%